Mitogen-Activated Protein Kinase 6 and Ethylene and Auxin Signaling Pathways Are Involved in Arabidopsis Root-System Architecture Alterations by Trichoderma atroviride - Hexon Angel Contreras-Cornejo; Jesús Salvador López-Bucio; Alejandro Méndez-Bravo; Lourdes Macías-Rodríguez; Maricela Ramos-Vega; Ángel Arturo Guevara-García; José López-Bucio (Molecular Plant-Microbe Interactions, 2015)
Trichoderma atroviride is a symbiotic fungus that interacts with roots and stimulates plant growth and defense. Here, we show that Arabidopsis seedlings cocultivated with T. atroviride have an altered root architecture and greater biomass compared with axenically grown seedlings. These effects correlate with increased activity of mitogen-activated protein kinase 6 (MPK6). The primary roots of mpk6 mutants showed an enhanced growth inhibition by T. atroviride when compared with wild-type (WT) plants, while T. atroviride increases MPK6 activity in WT roots. It was also found that T. atroviride produces ethylene (ET), which increases with l-methionine supply to the fungal growth medium. Analysis of growth and development of WT seedlings and etr1, ein2, and ein3 ET-related Arabidopsis mutants indicates a role for ET in root responses to the fungus, since etr1 and ein2 mutants show defective root-hair induction and enhanced primary-root growth inhibition when cocultivated with T. atroviride. Increased MPK6 activity was evidenced in roots of ctr1 mutants, which correlated with repression of primary root growth, thus connecting MPK6 signaling with an ET response pathway. Auxin-inducible gene expression analysis using the DR5:uidA reporter construct further revealed that ET affects auxin signaling through the central regulator CTR1 and that fungal-derived compounds, such as indole-3-acetic acid and indole-3-acetaldehyde, induce MPK6 activity. Our results suggest that T. atroviride likely alters root-system architecture modulating MPK6 activity and ET and auxin action.